Translation Learning through the Stylistic of Holy Qur'an - Harishul Ilmi; Mu'asshomah; Halimi Zuhdy (Asalibuna, 2025)
Abstract: This study aims to develop a translation teaching model based on Qur'anic linguistic styles to bridge the theoretical and practical gap in translation pedagogy. This research employed a qualitative descriptive-analytical approach through library research to analyze the style of QS. Al-'Alaq (1-5) as a pedagogical model. The findings reveal three main stylistic patterns: uslūb al-amr al-ta'līmī (educational imperative style in iqra' bi ismi rabbik) representing gentle pedagogical communication; uslūb al-takrār al-tarbawī (educational repetition) that reinforces meaning through reflection; and uslūb isti'ārah ta'līmiyyah (educational metaphor in 'allama bi al-qalam) emphasizing language symbolism as a means of knowledge transmission.Based on these findings, a "Qur'anic Translation Teaching Module" was formulated, consisting of four stages: understanding, analysis, translation, and reflection. Results indicate that applying Qur'anic styles in translation teaching develops three competencies: linguistic competence (mastery of Arabic morpho-syntactic structures and rhetorical devices), semantic competence (deep understanding of contextual meanings and intertextual relationships), and aesthetic-spiritual competence (sensitivity to stylistic beauty and spiritual dimensions of sacred texts).This research contributes to Arabic language pedagogy by offering a pedagogical model that integrates linguistic skills with moral and spiritual values, transforming translation teaching from a mechanical process into a transformational one that cultivates meaning sensitivity and spiritual awareness.   ملخص تهدف هذه الدراسة إلى تطوير نموذج لتدريس الترجمة يستند إلى الأساليب اللغوية القرآنية لسد الفجوة النظرية والعملية في تعليم الترجمة. استخدمت هذه الدراسة نهجًا وصفًا تحليليًا نوعيًا من خلال البحث المكتبي لتحليل أسلوب سورة العلق (1-5) كنموذج تعليمي. تكشف النتائج عن ثلاثة أنماط أسلوبية رئيسية: أسلوب الأمر التعليمي (في "اقرأ باسم ربك") الذي يمثل التواصل التربوي اللطيف؛ أسلوب التكرار التربوي الذي يعزز المعنى من خلال التفكير؛ و أسلوب الاستعارة التعليمية في "علّم بالقلم" الذي يؤكد على رمزية اللغة كوسيلة لنقل المعرفة. بناءً على هذه النتائج، تمت صياغة "وحدة تعليمية لترجمة القرآن" تتكون من أربع مراحل: الفهم والتحليل والترجمة والتفكير. تشير النتائج إلى أن تطبيق الأساليب القرآنية في تدريس الترجمة يطور ثلاث كفاءات: الكفاءة اللغوية (إتقان التراكيب الصرفية والنحوية العربية والأساليب البلاغية)، والكفاءة الدلالية (الفهم العميق للمعاني السياقية والعلاقات النصية)، والكفاءة الجمالية-الروحية (الحساسية تجاه الجمال الأسلوبي والأبعاد الروحية للنصوص المقدسة). تساهم هذه الدراسة في تعليم اللغة العربية من خلال تقديم نموذج تعليمي يدمج المهارات اللغوية مع القيم الأخلاقية والروحية، مما يحول تعليم الترجمة من مهمة.